2014
DOI: 10.1155/2014/250536
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Preoperative Counselling on Early Postoperative Mobilization and Its Role in Smooth Recovery

Abstract: Background and Objectives. Preoperative counseling is effective to foster early postoperative mobilization that reduces pulmonary complications following abdominal surgery. This study aims at evaluating the effect of preoperative counseling regarding postoperative mobilization and its impact on reducing pulmonary complications. Design and Setting. Randomized control trial was conducted at the Department of Surgery of a tertiary care hospital, Karachi. Patients and Materials. Patients who underwent abdominal su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 16 publications
(18 reference statements)
2
29
0
1
Order By: Relevance
“…It may not be how much physiotherapy that is important, but rather, when that physiotherapy is provided. The current weight of evidence appears to support the provision of a single preoperative physiotherapy education and DB&C training to all patients having abdominal surgery (Bourn et al 1991, Condie et al 1993, Denehy 2001, Fagevik Olsén et al 1997, Samnani et al 2014. Given the limitations of this research and the low incidence of PPCs following laparoscopic and LAS surgery, the authors recommend the provision of preoperative physiotherapy for all open UAS patients only.…”
Section: Preoperative Physiotherapy Interventions Preoperative Educationmentioning
confidence: 89%
See 3 more Smart Citations
“…It may not be how much physiotherapy that is important, but rather, when that physiotherapy is provided. The current weight of evidence appears to support the provision of a single preoperative physiotherapy education and DB&C training to all patients having abdominal surgery (Bourn et al 1991, Condie et al 1993, Denehy 2001, Fagevik Olsén et al 1997, Samnani et al 2014. Given the limitations of this research and the low incidence of PPCs following laparoscopic and LAS surgery, the authors recommend the provision of preoperative physiotherapy for all open UAS patients only.…”
Section: Preoperative Physiotherapy Interventions Preoperative Educationmentioning
confidence: 89%
“…The control group received no pre or postoperative physiotherapy. (Samnani et al 2014) of 232 abdominal surgery patients again demonstrated a significant reduction in PPCs from 30% to 7% (ARR 22%, 95%CI 13%-32%) when preoperative education focused on the importance of postoperative early ambulation compared to no education at all. Both groups were provided with similar postoperative care.…”
Section: Preoperative Physiotherapy Interventions Preoperative Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…The key recommendations of the ERAS guideline comprise preoperative patient information and counseling, no oral bowel preparation, no preoperative fasting, preoperative carbohydrate loading, no preanaesthetic medication, single dose antibiotic prophylax half an ______________________________ *Correspondence Yasemin Altınbaş Research Assistant Doctor,Department of Nursing, Adıyaman University School of Health, Adıyaman, Turkey E-Mail: yaltinbas@adiyaman.edu.tr hour before surgery, short incisions, avoidance of long acting opioids, mid-thoracic epidural anesthesia, paracetamol as baseline analgesic, avoidance of fluid overload, use of an upper-body forced-air heating cover, no drains, nonaso gastric decompression tubes, prevention of postoperative nausea and vomiting of high risk patients, standard laxatives, early removal of urinary bladder catheters, early oral nutrition and nutritional supplements and early mobilization [1,[5][6][7].Anesthesia, wounds, drains and pain are the inevitable results of surgical procedures and subordinates the patients to stay in bed for short or long periods and prevents patient's mobilization [7,8]. When the patients are not mobilized insulin resistance increases, muscles get weakened and muscle weight decreases.…”
Section: Introductionmentioning
confidence: 99%